Sand dunes of the Gaza Strip (southwestern Palestine): morphology, textural characteristics and associated environmental impacts (2014)
Sand dunes are wide spread in the Gaza Strip and are present in its northern, central and southern regions. Thirty sand samples were collected at seven locations along the middle region of the Strip. The coordinates for each sampling site were positioned using GPS and processed with ArcGIS software.Mechanical and chemical properties were examined to determine the textural characteristics and carbonate contents of the dune sands. The mean grain size is fine to medium, and the sands range from moderate- to well-sorting. The skewness is fine to very fine, and the kurtosis ranges from mesokurtic to very leptokurtic. Additionally, the results show that the carbonate content ranges from 1.5% to 5%.The high permeability, good porosity, and low carbonate content of the sand dunes in the Gaza Strip have led to more groundwater pollution via leachates percolating from the solid waste landfills and basins from wastewater treatments constructed above the sand dunes. Sand quarries have also changed the natural landscape of the Gaza Strip. These quarries were excavated randomly, used for a short period and then disused. This random and unregulated excavation has led to the destruction of natural habitats for flora and fauna. ResumenLas dunas de arena se extienden ampliamente en la Franja de Gaza y hacen presencia en las regiones del norte, centro y sur. Para este trabajo se recolectaron treinta muestras de arena en siete puntos a lo largo de la región media de la Franja. Las coordenadas de cada muestra se marcaron con el GPS y se procesaron con el programa ArcGIS. Se examinaron las propiedades químicas y mecánicas para determinar las características de textura y los contenidos de carbonato de las dunas de arena. El tamaño del grano está entre fino y medio y las arenas oscilan entre moderadas y bien definidas. La asimetría estadística va desde fina hasta muy fina y la variedad de la curtosis se ubica entre mesocúrtica y muy leptocúrtica. Adicionalmente, los resultados muestran que los rangos de contenido de carbonato están entre 1,5 % y 5 %. La alta permeabilidad, la buena porosidad y el bajo contenido de carbonato en las dunas de arena de la Franja de Gaza han permitido una mayor contaminación a través de lixiviados que se filtran desde vertederos de desechos sólidos y desde estaciones de tratamiento de aguas residuales construidas sobre las dunas de arena. Las canteras de arena, además, han cambiado el paisaje natural de la Franja de Gaza. Estas canteras fueron excavadas de manera aleatoria, utilizadas por un tiempo corto y luego cayeron en desuso. Estas excavaciones aleatorias y sin regulación han llevado a la destrucción de hábitats naturales de flora y fauna.